Miliarios romanos de la provincia de Pontevedra (Hispania citerior) - Abascal Palazón, Juan Manuel, 1958- (2020)
Las provincias de Pontevedra y Ourense concentran el mayor número de miliarios romanos de Galicia. Sin alcanzar las elevadas cifras de Ourense, de Pontevedra proceden 26 miliarios o fragmentos de ellos, que cubren un período de unos dos siglos y medio, entre los gobiernos de Nerva (96-98) y la usurpación de Magnencio y Decencio (350-353). En el conjunto destacan por su número las piezas de época de Adriano y las de Maximino el Tracio.
Most of Galicia’s roman milestones came from the provinces of Pontevedra and Ourense. Despite the high number of pieces from Ourense, 26 landmarks or fragments of them are found at Pontevedra, covering a period of about two and a half centuries, between the governments of Nerva (96-98) and the usurpation of Magnentius and Decentius (350-353). On the colletion, the milestones dated in the times of Hadrian and Maximinus the Thrax stand out for their number.
Keywords: Arquitectura romana; Pontevedra